Small buildings big improvements: addressing the need for community educational facilities in the informal city through provision of prototypical alternative learning and teaching spaces - Tod, Catherine Ann (School of Architecture, Planning and Geomatics, 2018)
Education, by its broadest definition, withholds and undeniable and indispensable potential for positive human development. This is particularly true in emerging economies where social and economic ills are rife. Addressing this issue is a meaningful step towards creating a more "equitable society" (VPUU, 2015) by providing a mechanism for emancipation. Individuals have a better chance of improving their quality of life with an educated mind. Contemporarily speaking, South Africa (an emerging economy) is enduring an educational crisis across many spheres that requires immediate attention. Due to historical disenfranchisement, many individuals have missed this fundamental human right and others (for numerous reason) have exited the system. These problems are ever prevalent to the poorer areas of the country, such as urban conditions like the South African township. The state institutions in these areas require support. Therefore, this inquiry seeks to address this issue. The design dissertation is fundamentally an exploration of teaching and learning space in the Informal City that sits outside the formal system - informal and alternative education - that serves to complement existing institutions. Informal educational space permits an ideal opportunity to experiment with new and innovative arrangements for educational operations and facilities in the South African township that provide a different spatial experience to conventional teaching and learning space. The architectural parameters can be extended.